Determinan Penggunaan Informasi Akuntansi dengan Ketidakpastian Lingkungan Sebagai Pemoderasi - Zuliyati, Zuliyati; Delima, Zamrud Mirah; Anisa, Faradina (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This study aims to examine the effect of business scale, company age, accounting knowledge, and educational background on the use of accounting information with environmental uncertainty as a moderating variabel. This type of research is quantitative. The population in this study is UKM in Jepara Regency. The sample used is 100 respondents. The analytical technique used is MRA. The result of this study indicates that business scale, company age, accounting knowledge, and educational background have no effect on the use of accounting information, and environmental uncertainty is not able to moderate the independent variabels in this study.